Performance parameters optimization of routing protocols for mobile ad hoc net-works based on taguchi approach - Lee, Muhammad Hisyam (Penerbit UTM, 2007)
This chapter presents the application of Taguchi approach in investigating the performance of mobile ad hoc networks (MANETs) with respect to drop rates. The performance of MANETs was in?uenced very much by the routing protocol designs and quantitative factors such as network size, terrain, pause-time, node speed, transmission range, tra?c load, and packet rates. The NS-2 simulator was used for the simulation of the MANETs under a speci?c scenario. The tools of Taguchi approach such as L12 orthogonal array, analysis of signal-to-noise ratio, and analysis of variance (ANOVA) were employed. Results showed that the e?ects of network size, terrain, node speed, transmission range, tra?c load, packet rates, and routing were found to be statistically signi?cant, and the most signi?cant factor was transmission range. Using the combination of optimal levels of the signi?cant factors, the speci?c values of drop rates was predicted. Good agreement between the predicted drop rates and actual drop rates was observed in this study.